BRIDGING CLASSROOM INSTRUCTION AND EMPLOYMENT DEMANDS: HOSPITALITY STUDENTS’ PERCEIVED READINESS FOR ENGLISH JOB INTERVIEWS - Andi Rizki Fauzi (RADJA PUBLIKA, 2025)
This qualitative inquiry explores hospitality students’ self-assessed preparedness for participating in English-mediated employment interviews within the international hospitality sector, emphasizing the mismatch between pedagogical practices in the classroom and the communicative realities of professional interviews. Data were collected through semi-structured, in-depth interviews involving 20 students enrolled at STIPARY Tourism Academy Yogyakarta, Indonesia. The interview data were subjected to thematic analysis guided by three pre-established analytical frameworks derived from the study objectives. The analysis identifies three overarching dimensions of readiness gaps. The first concerns affective constraints, where all participants exhibited interview-related anxiety, particularly when required to respond spontaneously. This affective burden was further compounded by limited command of hospitality-specific lexis and observable psychophysiological inhibition when facing high-pressure questioning. The second dimension relates to insufficient interview preparation, reflected in students’ unfamiliarity with the STAR interview framework, overdependence on rote memorization, and difficulty in producing logically organized and persuasive responses. The third dimension involves contextual inadequacies, notably a lack of awareness regarding intercultural interview conventions, appropriate register selection, and effective strategies for addressing challenging or sensitive questions. Despite its focus on a single Indonesian tourism institution, the study offers important pedagogical implications. The findings point to the urgency of integrating anxiety regulation strategies, explicit training in structured interview discourse, sustained practice in spontaneous spoken interaction, instruction in cross-cultural pragmatics, and closer collaboration with industry stakeholders through authentic HR-oriented feedback. This study extends the ESP and vocational ELT literature by revealing instances of complete communicative shutdown during interviews and by highlighting the discrepancy between students’ perceived self-marketing confidence and their actual oral proficiency.